T-Cell Mediated Immune Responses in Obstetric Population Acutely Infected With Toxoplasmosis in Kano, Nigeria - Ibrahim, A.,; Kumurya, A. S.; Yahaya, H.,; Abdu, A.,; Ado, B. K.,; Ella, E. E.; Suleiman, A. B.; Sulaiman, M. A.; Aminu, M. A; Koki, A. Y. (UMYU Journal of Microbiology Research)
Toxoplasmosis is a disease caused by an obligate intracellular protozoan parasite Toxoplasma gondii which is endemic worldwide.. There is paucity of reports on the immunological responses of pregnant women to toxoplasmosis in Kano. This study was carried to determine T-cell mediated immune responses in pregnant women with acute toxoplasmosis in Kano and factors associated with seropositivity. A total of 320 blood samples were collected and assayed for anti- Toxoplasma gondii Immunoglobulin M (IgM) antibody using ELISA test kit. Samples were assayed for CD4, CD8, using BDFACSCount and the cytokines interferon-gamma (IFN-ϒ), tumour necrosis factor-alpha (TNF-α) using ELISA test kits while differential leucocytes count was carried out microscopically by Leishman staining technique. The IgM seroprevalence was 24(7.5%) and 296(92.5%) were negative. Associated risk factors were cat ownership and consumption of unwashed vegetables (p values = 0.0014 and 0.001 respectively). Mean CD4, CD8, CD4:CD8 and differential count were within normal range for the study subjects with no statistically significant relationship across trimesters. IFN-ϒ and TNF-α were elevated. Moderate eosinophilia appeared with statistically significant relationship between lymphocyte and neutrophil counts across trimesters ( p value = 0.0278). The immunomodulatory effect of pregnancy does not classically suppress T-cell mediated immune responses as our findings revealed normal but slightly reduced distribution of CD4 and CD8 cell counts with elevated IFN- ϒ and TNF-α. The findings revealed the immune status of the study subjects, as slightly modulated, nonetheless, it is urgent to offer adequate health education programs on toxoplasmosis to pregnant women yet to be infected on how to prevent the infection so as to avoid occurrence of congenital infection.